Gift theory as cultural theory: reconciling the ir/religious - Manolopoulos, Mark (Culture and religion, 2007)
What if thinking the gift could offer a way of rethinking two of society's most irreconcilable cultural spheres - the religious and the irreligious? The gift is irreducibly dual, marked by both gratuity and reciprocity, excess and exchange. What, then, if creation is a gift? (The "ifness" of the proposition is duly acknowledged, discussed, and affirmed.) Religious responses to the possible gift of creation may be interpreted as reflecting and respecting the circular dimension involved in gifting (religion as thanking and reciprocating), while secular-hedonistic responses reflect and respect its gratuity (irreligion as taking and enjoying).